On Not Writing a Review about Mirador: Mirador, IIIF, and the Epistemological Gains of Distributed Digital Scholarly Resources. Issue 1 (3rd August 2018) - van Zundert, Joris
Abstract : This piece mushroomed from a simple enough looking suggestion to write a review about Mirador, a viewer component for web based image resources. While playing around and testing Mirador however, a lot of questions started to emerge–questions that in a scholarly sense were more significant than just the functional requirements of textual scholars and researchers of medieval sources for an image viewer. These questions are forced upon us because of the way Mirador is built, and by the assumptions it thereby makes–or that its developers make–about its role and about the larger infrastructure for scholarly resources that it is supposed to be a part of. This again led to a number of epistemological issues in the realm of digital textual scholarship. And so, what was intended as a simple review resulted in a long read about Mirador, about its technological context, and about digital scholarly editions as distributed resources. The first part of my story gives a straightforward review-like overview of Mirador. I then delve into the reasons that I think exist for the architectural nature of the majority of current digital scholarly editions, which are still mostly monolithic data silos. This in turn leads to some epistemological questions about digital scholarly editions. Subsequently I return to Mirador to investigate whether its architectural assumptions provide an answer to these epistemological issues. To estimate whether the epistemological "promise" that Mirador's architecture holds may be easily attained, I gauge what (technical) effort is associated with building a digital edition that actually utilizes Mirador. Integrating Mirador also implies adopting the emerging standard IIIF (international image interoperability framework); a discussion of this "standard-to-be" is therefore in order. Finally the article considers the prospects of aligning the IIIF and TEI "standards" to further the creation of distributed digital scholarly editions.